Beyond Smoke and Mirrors : Climate Change and Energy in the 21st Century. - Richter, Burton (Cambridge University Press, 2010)
Nobel Prize-winning scientist's assessment of options for switching to sustainable energy provision to avert potentially disastrous consequences of climate change.